Determinan Minat Berkarir Sebagai Akuntan Pajak: Studi Empiris pada Mahasiswa Akuntansi di Kota Mataram - M. Zainul Majdi; Adhitya Bayu Suryantara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the factors that influence the interest of accounting students in Mataram in pursuing a career as a tax accountant. The factors studied include motivation, financial rewards, tax knowledge, self-efficacy, and mastery of technology. By using Partial Least Square (PLS) analysis and a sample of 131 respondents, the research results show that motivation and knowledge of taxation have a significant influence on students' interest in pursuing a career in taxation. Students who have high motivation and a strong understanding of taxation tend to choose this career path. However, financial rewards, self-efficacy, and mastery of technology do not have a significant effect on career interest. These findings suggest that intrinsic factors, such as motivation and competence, play a greater role in shaping career interests, while extrinsic factors such as financial rewards and technology are considered secondary considerations.